Splenectomy modulates intrarenal B cell differentiation and impairs repair of post-ischemic kidney - Lee, Kyungho; Jeon, Hojin; Lee, Kyung Sub; Jeon, Junseok; Lee, Jung Eun; Kwon, Ghee Young; Huh, Wooseong; Jang, Hye Ryoun (Frontiers in Immunology, 2025)
IntroductionLymphocytes are known to regulate kidney repair after ischemia-reperfusion injury (IRI). Splenectomy has been proposed as a preconditioning protocol for high-risk kidney transplantation and has been suggested to affect IRI outcomes. However, the role of splenectomy in IRI repair remains poorly understood. This study investigated the effects of splenectomy on the immunological microenvironment in a mouse model of kidney IRI.MethodsC57BL/6 mice underwent severe (45 min) unilateral (left) IRI and were divided into two groups: IRI surgery alone (IRI group) and IRI surgery with simultaneous splenectomy (IRI+SPX group). Post-ischemic and contralateral kidneys were collected on days 10 and 30 after IRI. Kidney function, histology, lymphocyte population (analyzed by flow cytometry), and cytokine/chemokine expression were evaluated.ResultsThe plasma creatinine levels were higher in the IRI+SPX group on day 10, while the cystatin C concentrations were not significantly different between the two groups. The percentage of tubular damage and fibrosis in post-ischemic kidneys during the repair phase was significantly higher in the IRI+SPX group than in the IRI group. While the T cell profiles were comparable between the groups, the proportions of activated B cells and MHCII+ B cells in the post-ischemic and contralateral kidneys were higher in the IRI+SPX group on day 30 after IRI. The expressions of IL-17, MCP-1, and TGF-β in post-ischemic kidneys were higher in the IRI+SPX group compared with the IRI group. DiscussionSplenectomy exacerbates tubular damage and fibrosis during the repair phase of severe IRI and significantly alters the immunological microenvironment of the kidneys, promoting B cell differentiation. Our study suggests that splenectomy may worsen outcomes in IRI, and further studies investigating potential reparative pathways through the kidney–spleen axis are warranted.